Edukasi ASI Eksklusif Untuk Persiapan Menyusui Menjelang Persalinan: Edukasi ASI Eksklusif Untuk Persiapan Menyusui Menjelang Persalinan - Mirawati Mirawati; Rr. Sri Nuriaty Masdiputri; Mahfuzhah Deswita Puteri; Tasya Hikmah; Fatmawati Fatmawati (Yayasan Ahmad Mansyur Nasirah, 2022)
Mother's milk is an excellent source of nutrition for babies, breast milk has a balanced composition and according to the needs of the baby's growth. There are several areas in South Kalimantan where the coverage of exclusive breastfeeding is still low. In the Banjar Regency area, the coverage of exclusive breastfeeding reached 82.1% in 2020 and in one of the sub-districts, the coverage ratio was more than 47%. Failure to give exclusive breastfeeding, has the potential to cause nutritional deficiencies in infants. This community service aims to increase knowledge about exclusive breastfeeding so that awareness is formed in preparation for breastfeeding before birth. The participants in this activity amounted to 13 pregnant women and 9 accompanying families, so there were a total of 22 participants. The implementation method used is counseling with lectures and discussions as well as demonstrations on how to breastfeed properly and correctly. The conclusion that can be drawn from this activity is that there is an increase in knowledge about exclusive breastfeeding and good and correct breastfeeding skills. Respondents with good knowledge increased from 36.4% to 63.6%. Hopefully this community service can help create a healthy and intelligent generation with exclusive breastfeeding.